2015
DOI: 10.1073/pnas.1514478112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pressure on the dynamics of an oligomeric protein from deep-sea hyperthermophile

Abstract: Inorganic pyrophosphatase (IPPase) from Thermococcus thioreducens is a large oligomeric protein derived from a hyperthermophilic microorganism that is found near hydrothermal vents deep under the sea, where the pressure is up to 100 MPa (1 kbar). It has attracted great interest in biophysical research because of its high activity under extreme conditions in the seabed. In this study, we use the quasielastic neutron scattering (QENS) technique to investigate the effects of pressure on the conformational flexibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
38
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 75 publications
(120 reference statements)
4
38
0
1
Order By: Relevance
“…The MCT was originally developed to describe the complex dynamics in glass-forming liquids (4042), but has been successfully used in predicting the logarithmic-like decay in β -relaxation dynamics of globular proteins and other biopolymers (22, 38, 39, 43). The ISFs with logarithmic-like decay behavior can be fitted with an asymptotic expression derived from the MCT: I(Q,t)=f(Q,T)-H1(Q,T)ln[t/τβ(T)]+H2(Q,T)ln2[t/τβ(T)]…”
Section: Resultsmentioning
confidence: 99%
“…The MCT was originally developed to describe the complex dynamics in glass-forming liquids (4042), but has been successfully used in predicting the logarithmic-like decay in β -relaxation dynamics of globular proteins and other biopolymers (22, 38, 39, 43). The ISFs with logarithmic-like decay behavior can be fitted with an asymptotic expression derived from the MCT: I(Q,t)=f(Q,T)-H1(Q,T)ln[t/τβ(T)]+H2(Q,T)ln2[t/τβ(T)]…”
Section: Resultsmentioning
confidence: 99%
“…[18] Pressure-driven conformational changes may increase enzyme activity through β and α-relaxations. [19] These small changes can lead to the acquisition of protein conformations more suited for catalysis. [18] …”
mentioning
confidence: 99%
“…However, there appears to be no universal adaptive mechanism, but rather a complex combination of different factors, which frequently differs according to the protein or protein family and is thus difficult to generalize 8,10 . Furthermore, the role of dynamic characteristics such as conformational stability 11 12 and flexibility 13 , for protein adaptability is still not well understood 1,14 .Recent studies have reported that the conformational sub-states of a protein are significantly perturbed by changes in temperature and pressure 13,[15][16][17][18][19] . Temperature enhances the internal fluctuations of a protein 20 , and an optimum temperature may provide an appropriate balance of flexibility and rigidity required for function 13,21,22 .…”
mentioning
confidence: 99%
“…Furthermore, the role of dynamic characteristics such as conformational stability 11 12 and flexibility 13 , for protein adaptability is still not well understood 1,14 .Recent studies have reported that the conformational sub-states of a protein are significantly perturbed by changes in temperature and pressure 13,[15][16][17][18][19] . Temperature enhances the internal fluctuations of a protein 20 , and an optimum temperature may provide an appropriate balance of flexibility and rigidity required for function 13,21,22 . Temperatures higher than the optimum can lead to loss of function through unfolding or denaturation 23 .…”
mentioning
confidence: 99%